Transmission Electron Microscopy of the Presbylarynx in the Process of Voice Aging - Gonçalves, Tatiana Maria [UNESP]; Martins, Regina Helena Garcia [UNESP]; Adriana, Bueno Benito Pessin [UNESP] (Elsevier, 2018)
Introduction: Microscopy studies of presbylarynx have identified epithelial atrophy, as well as vocal muscle atrophy, increased collagen, and decreased nonfibrous proteins of the extracellular matrix. Studies on the ultrastructure of presbylarynx are rare and can help us understand the pathophysiology of presbyphonia. Objective: To describe details on the ultrastructure of presbylarynx by transmission electron microscopy (TEM). Subjects and Methods: Sixteen human larynges were removed and distributed in two groups: control (n = 8; 30–50 years; six females, two males) and seniors (n = 8; 75–92 years; six females, two males). After preparation for TEM, the specimens, including epithelium and lamina propria, were examined and photographed at increasing magnification. Results: Control: the epithelium was intact, with overlapped cells, and with desmosomes between the intercellular junctions. The basement membrane was continuous and uniform, and the lamina propria contained collagen and elastic fibers in a regularly distributed loose arrangement, as well as some fibroblasts of different shapes. Senior: the epithelial cells were separated by enlarged intercellular junctions. The basement membrane was delicate and continuous. In the lamina propria there was predominance of elongated fibroblasts. Under the basement membrane a dense network of collagen fibers could be identified. Conclusions: In this study with TEM some structural changes were identified, particularly in the larynx of the elderly, both in the epithelium and lamina propria, some of them with likely participation of fibroblasts, which reinforces the importance of additional ultrastructure as well as molecular studies targeting those cells, as they are the main precursors of the components of the extracellular matrix.
Keywords: Aging voice; Elderly; Presbylarynx; Transmission electron microscopy; Ultrastructure